Research Progress on Microbial Diversity, Evaluation and Maintenance of Baijiu Pit Mud - ZOU Fei, YE Li, FENG Liang, ZHENG Xiaowei, HUANG Biao, XIA Bing, ZHANG Wuji, CHEN Xiaoyuan, FANG Zhengguo, SUN Yuting (Shipin Kexue, 2024)
Solid-state fermentation in mud pits is a typical brewing process for nongxiangxing baijiu and fuyuxiangxing baijiu. Pit mud is the functional carrier of mud pits, in which the abundance, diversity, metabolic activity and interaction of microorganisms could directly affect the quality of baijiu. This paper reviews the application of traditional culture and non-culture techniques in research on microorganisms in pit mud, the spatiotemporal differences in microbial community structure, the functional microorganisms and their interactions, the development and improvement of the methods for the quality evaluation of pit mud, and pit mud maintenance and aging focusing on the functional strains, and summarizes the development history and application status of different techniques in the field of research on microorganisms related to the production of Chinese baijiu, the growth and decline patterns of prokaryotic and eukaryotic microorganisms during pit mud aging, the spatial difference in the distribution of prokaryotic and eukaryotic microorganisms in the pit, and the functions and interdependence of the core functional microorganisms in pit mud such as caproic acid bacteria, butyric acid bacteria, lactic acid bacteria, acetic acid bacteria and methane bacteria, the reason for pit mud aging, the transformation of the criteria for quality evaluation pit mud from traditional sensory and physicochemical analysis to the comprehensive evaluation system, and studies on pit mud maintenance and aging based on the functional properties of core strains. The purpose of this review is to provide a reference for evaluating the microbial diversity, exploring the metabolic function of microbial community and improving the quality of pit mud.